Complete Remission of a Refractory Acute Myeloid Leukemia with Myelodysplastic- and Monosomy 7-Related Changes after a Combined Conditioning Regimen of Plerixafor, Cytarabine and Melphalan in a 4-Year-Old Boy: A Case Report and Review of Literature. - Grasso, Antonio G; Granzotto, Marilena; Zanon, Davide; Maestro, Alessandra; Loiacono, Stefano; Maximova, Natalia (Cancers (Basel), 2018)
Acute myeloid leukemia with myelodysplastic changes and monosomy 7 is a rare form of pediatric leukemia associated with very poor disease-free survival. The refractoriness of the disease is due to the protection offered by the bone marrow niche, making leukemic stem cells impervious to whatever chemotherapy or myeloablative regimen is chosen. Using a mobilizing agent for haematopoietic stem cells, Plerixafor, could sensitise leukemic cells to the myeloablative therapy. This approach was not previously used in a pediatric population, and in adult populations, was used in combination with busulphan with no difference in overall survival. We describe the case of a 4-year-old boy affected by refractory acute myeloid leukemia with myelodysplastic changes and monosomy 7. The child had never achieved a remission. We proposed a combined time-scheduled scheme of therapy with plerixafor and melphalan. Combining pharmacokinetics of plerixafor with pharmacokinetics and rapid and elevated myeloablative potential of melphalan in high dosage (200 mg/m²), we succeeded in mobilizing more than 85% of stem blasts immediately before infusion of Melphalan. The count of residual blasts after 8 h from melphalan infusion was only 1.3 cells/μL. The child achieved an engraftment at day +32 with full donor chimerism. Sixteen months after haematopoietic stem cell transplantation (HSCT), he is well and in complete remission. Our case suggests that the use of plerixafor before a conditioning therapy with melphalan could induce remission in acute myeloid leukemia refractory to the usual conditioning therapy in pediatric patients. This work adds strength to the body of knowledge regarding the "personalized" conditioning regimen for high-risk leukemic patients.

Comparison of Efficacy and Safety of Caspofungin Versus Micafungin in Pediatric Allogeneic Stem Cell Transplant Recipients: A Retrospective Analysis. - Maximova, Natalia; Schillani, Giulia; Simeone, Roberto; Maestro, Alessandra; Zanon, Davide (Adv Ther, 2017)
INTRODUCTION: The high morbidity and mortality associated with invasive fungal infections (IFIs) provide the rationale for antifungal prophylaxis in immuno-compromised pediatric patients undergoing hematopoietic stem cell transplantation (HSCT). Caspofungin and micafungin are antifungal agents of interest for prophylaxis of IFIs because of their potency against Candida and minimal toxicity or interactions with other drugs. Few studies have demonstrated the safety and efficacy of such echinocandins as prophylaxis for IFIs in patients undergoing HSCT. METHODS: This retrospective cohort study compared caspofungin and micafungin for prevention of IFIs in 93 pediatric patients undergoing HSCT for oncological or non-oncological disease. The observation began with the first dose of antifungal agent and ended 3 months after transplantation. RESULTS: Patients in the micafungin group had a higher overall treatment success rate of 87.2 versus 84.8% in the caspofungin group, but the difference was not significant. There were no statistically significant differences in the incidence or type of proven/probable IFIs between the 2 groups. The low incidence of death did not differ statistically between the groups. Patients in the caspofungin group presented more frequently with fever, during and after neutropenia. In both groups, we observed an expected worsening of blood chemistry parameters. There were no adverse events definitely attributable to the two antifungal agents. CONCLUSION: These results demonstrate good efficacy and tolerability for caspofungin and micafungin. However, better results with respect to the incidence and resolution of fever in the micafungin group may suggest its use in preference to that of caspofungin.
Keywords: Adolescent; Antifungal Agents; Caspofungin; Child; Child, Preschool; Cohort Studies; Echinocandins; Female; Hematopoietic Stem Cell Transplantation; Humans; Infant; Infant, Newborn; Lipopeptides; Male; Micafungin; Mycoses; Neutropenia; Retrospective Studies

Does Teno Torque Virus Induce Autoimmunity After Hematopoietic Stem Cell Transplantation? A Case Report. - Maximova, Natalia; Pizzol, Antonio; Ferrara, Giovanna; Maestro, Alessandra; Tamaro, Paolo (J Pediatr Hematol Oncol, 2015)
Teno Torque virus, member of the family of Anelloviridae, has been associated with many autoimmune diseases such as idiopathic hepatitis, systemic lupus erythematosus, and multiple sclerosis. Its viral load tends to be higher in the bone marrow and in tissues with high turnover rate. We report here a case of an 11-month-old infant affected by acute myeloid leukemia who underwent hematopoietic stem cell transplantation, and after 6 months had autoimmune hepatitis and atopic dermatitis. Extremely high-cytokine IP-10 and eotaxin levels were found in her sera, and serological tests and RT-PCR for viruses showed positive results exclusively for Teno Torque virus.
Keywords: Autoimmune Diseases; Autoimmunity; Dermatitis, Atopic; DNA Virus Infections; DNA, Viral; Female; Hematopoietic Stem Cell Transplantation; Hepatitis; Humans; Infant; Leukemia, Myeloid, Acute; Prognosis; Torque teno virus; Viral Load

A web-based system for total parenteral nutrition prescription in a pediatric hospital - biomed 2010. - Bava, Michele; Bradashia, Fulvio; Rovere, Francesca; Maestro, Alessandra; Vecchi Brumatti, Liz; Accardo, Agostino; Paparazzo, Rossella; Zanon, Davide (Biomed Sci Instrum, 2010)
otal Parenteral Nutrition (TPN) is defined as feeding a patient by infusing nutrients intravenously, bypassing the usual process of eating and digestion. There are two kinds of TPN: short-term TPN may be used when a patient's digestive system is temporarily nonfunctional because of an interruption in its continuity; long-term TPN is used to treat patients with an impairment or a lack in nutrient absorption. TPN has extended the life of children born with nonexistent or severely deformed digestive organs and is a vital support for these patients. In Burlos Pediatric Department, pediatricians fill in a pharmacy request form in which nutritional needs are included for each patient. Subsequently, clinical pharmacists evaluate the patients individual data and decide which TPN formula to prepare. To enhance the TPN prescription process, an intranet web-based system has been developed to replicate the original paper-based forms. The software, developed in PHP and based on open source tools and services, has been constructed according to pharmacists requirements. These professionals, together with the Hospital Information System technicians, thanks to the availability of affordable instruments, perceive the advantages that such a system would have in improving clinical practice and quality of care. The system was devised with the goal to avoid common reading errors, to improve the correct text comprehension, to ensure prescription preparation, administration and tracking. According to a process of total quality control, the system reduces clinical risks regarding issues such as the correct and rapid availability of medical prescriptions and the incorrect identification of the patients. In comparison with paper-based TPN prescriptions, electronic-based forms have reduced the incidence of errors, the possible lack of patient data and reading misunderstandings. Regarding future improvements, IT technicians are defining the procedures to implement digital signature and medical aspects of the electronic TPN medical prescriptions.